COMPARATIVE ANALYSIS OF WORD FORMATION AND PARTICLE OF LANGUAGE ON ANGKOLA BARUMUN AND ANGKOLA TAPANULI SELATAN LANGUAGE WRITTEN TEXT TAKEN FROM WA SCRIPT - Syukri, Habib (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2024)
Angkola languages consisted of some regional such as Angkola Sipirok, Angkola Batangtoru, Angkola Padang Lawas, Angkola Barumun, and Angkola MuaraTais. In this research, the researcher compare and analyze Angkola Barumun and Angkola Tapanuli Selatan (Sipirok), in word formation process and particles of language. Research of the word formation process and particles of langage is interesting to study since these languages is a very special languages in western North Sumatera. The method of the research is descriptive qualitative method, the data was taken from some informants or native speakers of Angkola Barumun and Angkola Tapanuli Selatan through their chat in whats app  group. Their chating in written form was analyzed to search out the types of word formations and particles in Angkola Barumun and Angkola Tapanuli Selatan language. The findings showed that the word formation process occurred in three processes, namely blending, derivation, and back formation. Here, derivation dominate the other processes which occurred in six words. The back formation processes occurred in five words, followed by the derivation processes with three words. Nevertheless, the clipping, acronym, coinage, and borrowing processes were not found in this study. Meanwhile, the particles of language in Angkola Barumun and Angkola Tapanuli Selatan language were du (do), pe, ma, as based on the native speakers’ written text on their script.